The Relationship Between Anemia in Pregnant Women and the Incidence of Low Birth Weight Post-Health Crisis Conditions at the Sitti Khadijah 1 Mother and Child Hospital Makassar in 2024 - Puspita, Winda Dwi; Arlina, Andi; Putri, Ayu Syah; Kalsum, Umi; Sulastri, Nia (JURNAL KESEHATAN DELIMA PELAMONIA, 2024)
Background: Anemia in pregnancy causes oxygenation and maternal nutrient supply to the fetus, which causes the fetus to experience impaired weight gain, which causes premature birth and LBW. According to the World Health Organization (WHO) 2023, there were 111,729 babies, or 2.5% of LBW babies in Indonesia. The Purpose: To determine whether there is a relationship between anemia in mothers and the incidence of LBW after a health crisis situation at the Sitti Khadijah 1 Mother and Child Hospital, Makassar. Methods used in this study is quantitative with a descriptive approach, the total sampling technique used with a sample size of 43. Conclusion of the study showed a relationship between anemia in pregnant women with LBW cases after the health crisis at RSIA Sitti Khadijah 1 Makassar.